Moderate Weight Reduction in an Outpatient Obesity Intervention Program Significantly Reduces Insulin Resistance and Risk Factors for Cardiovascular Disease in Severely Obese Adolescents - J. Grulich-Henn; S. Lichtenstein; F. Hörster; G. F. Hoffmann; P. P. Nawroth; A. Hamann (International Journal of Endocrinology)
Background. Metabolic risk factors like insulin resistance and dyslipidemia are frequently observed in severly obese children. We investigated the hypothesis that moderate weight reduction by a low-threshold intervention is already able to reduce insulin resistance and cardiovascular risk factors in severely obese children. Methods. A group of 58 severely obese children and adolescents between 8 and 17 years participating in a six-month-long outpatient program was studied before and after treatment. The program included behavioral treatment, dietary education and specific physical training. Metabolic parameters were measured in the fasting state, insulin resistance was evaluated in an oral glucose tolerance test. Results. Mean standard deviation score of the body mass index (SDS-BMI) in the study group dropped significantly from +2.5 ± 0.5 to 2.3 ± 0.6 (P<0.0001) after participation in the program. A significant decrease was observed in HOMA (6.3 ± 4.2 versus 4.9 ± 2.4, P<0.03, and in peak insulin levels (232.7 ± 132.4 versus 179.2 ± 73.3 μU/mL, P<0.006). Significant reductions were also observed in mean levels of hemoglobin A1c, total cholesterol and LDL cholesterol. Conclusions. These data demonstrate that already moderate weight reduction is able to decrease insulin resistance and dyslipidemia in severely obese children and adolescents.